Adaptation and Validation of the Self-Administered Foot Health Assessment Instrument for Portuguese Undergraduate Nursing Students - Bernardes, Rafael A. (Springer Nature, 2025)
Background and Purpose: To translate and adapt the Self-Administered Foot Health Assessment Instrument from English to European Portuguese and explore its reliability and validity among undergraduate nursing students in Portugal.
Methods: The study was divided into two phases. First, the translation and cross-cultural adaptation followed Beaton's guidelines, with a pretesting of the final version with 30 students. The validation process used the content validity index with a minimum of 75% agreement between experts and Cronbach's alpha for internal consistency. The second step provided the results of the principal component analysis and confirmatory factor analysis, which were performed to study the overall fit of the model and item correlations. The STROBE checklist was used.
Results: The Portuguese version, Instrumento de Auto-Avaliação da Saúde do Pé (IAASP), showed an overall acceptable evidence regarding content validity and internal consistency. The factor analysis results suggested removing the "Foot pain" dimension from the original scale.
Conclusions: IAASP is suggested to maintain the original 22-item structure, with four domains, "Skin health," "Nail health," "Foot structure," and "Foot pain," being an initial reliable version with interest to measure the current foot health of nursing students. Future studies should contribute to IAASP's continuous improvement.